Thinking through story: Archaeology and narratives. Issue 3 (December 2016) - Porr, Martin; Matthews, Jacqueline
Abstract : In this paper – which also serves as an introduction to this special issue of Hunter Gatherer Research – we concentrate on a number of aspects relevant to the relationships between archaeology and narratives, and also to the theoretical and methodological challenges of research involving hunting and gathering societies. We focus on the 'narrative turn', which became influential across a range of disciplines due to the shift it introduced from a story being the sole focus of analysis to 'the lamp by which other things are seen' (Kreiswirth 1994:62). Working with a narrative approach, we consider how archaeologists have framed the relationship between hunting and gathering people and their environments, and in contrast, discuss the ways that contemporary Indigenous people themselves explain these relationships and the importance of narrative in understanding such relationships. Further, we critically discuss the way narrative or storytelling has been positioned in human cognitive evolution and in establishing human 'uniqueness', highlighting some problematic ongoing trends in Western scholarship. These examples led us to question the relationship between knowledge, myth and reality, particularly in the context of the relationship between the Western academy and Indigenous knowledge. We close this paper by drawing together the implications for narratives of human evolution and hunter-gatherer archaeology. Even though, or perhaps because, a narrative approach challenges the status quo we find that it offers many advantages to better understand the past and also to enhance reflexivity in the present.